2016
DOI: 10.1038/srep39530
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira surface adhesin (Lsa21) induces Toll like receptor 2 and 4 mediated inflammatory responses in macrophages

Abstract: Leptospirosis is zoonotic and emerging infectious disease of global importance. Little is understood about Leptospira pathogenesis and host immune response. In the present work we have investigated how Leptospira modulates the host innate immune response mediated by Toll-like receptors (TLRs) via surface exposed proteins. We screened Leptospira outer membrane/surface proteins for their ability to activate/inhibit TLR2/4 signaling in HEK293 cell lines. Of these the 21 kDa Leptospira surface adhesin, Lsa21 had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Lymphocyte proliferation assay was performed as previously described with minor modifications [ 26 ]. Splenocytes were prepared as previously described [ 27 , 28 ]. Samples were centrifuged 5 min at 300 rpm/ min and splenocytes were suspended with RPMI incomplete medium.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphocyte proliferation assay was performed as previously described with minor modifications [ 26 ]. Splenocytes were prepared as previously described [ 27 , 28 ]. Samples were centrifuged 5 min at 300 rpm/ min and splenocytes were suspended with RPMI incomplete medium.…”
Section: Methodsmentioning
confidence: 99%
“…Recent publications show that different leptospiral proteins (hemolysins [36] and Lsa21 [37]) are TLR2 and TLR4 agonists. It is highly probable that these data are misleading since experiments were performed with recombinant proteins produced in E. coli, a bacterium expressing one of the most potent LPS.…”
Section: Toll-like Receptor (Tlr) and Nod-like Receptor (Nlr) Speciesmentioning
confidence: 99%
“…It has been shown that TLR4 plays a critical role in controlling bacterial load and the development of severe leptospirosis in mice 71 .Thus, it is likely that those surface proteins and LPS which are natural ligands of these receptors and can activate macrophages and DCs, might undergo variations thereby enabling the bacteria to evade this innate recognition and adhere to the host. Several surface proteins of Leptospira have been identified as ligands of TLR2 or TLR4 that are capable of activating innate immune response and are potential vaccine candidates 3437,72 . Lig proteins are important virulence factors and its expression during infection or loss of its expression during in vitro culture has been correlated to virulence of the infecting serovar 52,56,73 .…”
Section: Discussionmentioning
confidence: 99%